RESEARCH UPTAKE: THE VALUE OF EFFECTIVELY COMMUNICATING RESEARCH TO YOUR AUDIENCE - Nguyen, Dori (European Scientific Journal, ESJ, 2014)
The field of research uptake is an emerging, yet imperative area of ‘meta’ research – insight into different approaches on disseminating and using research is continually surfacing. These include strategies on how to catch, maintain and sustain the attention of target audiences, ensure that knowledge is appropriately transferred to policymakers, practitioners and other end users, and monitoring its impact. Extensive literature, coupled by a variety of tools, both generic and topic-specific, exists dedicated to helping the researcher research and integrate dissemination plans into their work. These often aim to increase communication and understanding across disciplines and appropriately affect policy, society, culture and environment. This paper attempts to define some key terminology, provide a brief introduction to ongoing efforts and explore some main motivations and justifications for integrating uptake into research.